PERUBAHAN NILAI BUDAYA URANG BANJAR (DALAM PERSFEKTIF TEORI TROOMPENAAR) - Parhani, Imadduddin (Pascasarjana UIN ANTASARI Banjarmasin, 2016)
Cultural Values Urang Banjar research has not been done. This study refers to the dimension of cultural values being addressed Troompenaar. According Troompenaar cultural values have seven dimensions: individualism - Communitarism, specifik Relationship - Diffuse relationship, Universalism - Particularism, Neutral Relationship - Emotional Relationship, Achivemenent - ascription, Sequential time - Synchoronous time, and the Environment. Results of research conducted Troompenaar in Indonesia, indicating Indonesia is in the category Communitarism, Diffuse relationship, Particularism, Neutral Relationship, ascription, Synchoronous Time and Outter Direction. This study uses primary data collected through questionnaires which had been prepared previously by the indicators Troompenar dimensions of cultural values. The total sample was 192 people. The research focuses on is the Banjar, and its relation to the cultural values of Banjar. The conclusion of this research are (1) The value of Banjar culture included in the category of universalism with a percentage of 78.13 percent, Komunitariasme with the percentage of 79.17 percent, with the percentage Emotional 73, Specification with the percentage of 54.17 percent, with the percentage of 76.04 percent Achievement, synchronous with the percentage of 69, 79 percent, and Outter direction with the percentage of 83.33 percent; (2) There was a difference or shift in cultural values in society Banjar with Indonesian cultural values, from particularism into Universalism, from Neutral became Emotional, of Diffuse be Specific, and of ascription becomes Achievement; (3) The difference in the value of Indonesian culture and cultural values Urang Banjar indicate that changes peoples lives, especially people Banjar ongoing and will never stop, because no one masyarakatpun that stops at a certain point all time. The difference or shift in cultural values that occurred in Banjar Urang an ongoing process of social change in society Banjar.